Hybrid top-down and bottom-up interprocedural analysis - Zhang, X; Mangal, R; Naik, M; Yang, H (Association for Computing Machinery, 2014)
Interprocedural static analyses are broadly classified into top-down and bottom-up, depending upon how they compute, instantiate, and reuse procedure summaries. Both kinds of analyses are challenging to scale: top-down analyses are hindered by ineffective reuse of summaries whereas bottom-up analyses are hindered by inefficient computation and instantiation of summaries. This paper presents a hybrid approach SWIFT that combines top-down and bottomup analyses in a manner that gains their benefits without suffering their drawbacks. SWIFT is general in that it is parametrized by the top-down and bottom-up analyses it combines. We show an instantiation of SWIFT on a type-state analysis and evaluate it on a suite of 12 Java programs of size 60-250 KLOC each. SWIFT outperforms both conventional approaches, finishing on all the programs while both of those approaches fail on the larger programs